Importance of regional diversity and environmental conditions on local species richness of aquatic macro-invertebrates in tropical forested streams. (14th May 2014) - Al-Shami, Salman Abdo; Md Rawi, Che Salmah; Ahmad, Abu Hassan; Madrus, Madziatul Rosemahanie; AL Mutairi, Khalid
Abstract: We used aquatic macro-invertebrates as a model to investigate the relationship between the regional species richness (RSR) and local species richness (LSR) in Peninsular Malaysia. A total of 38 streams (local scale) in seven catchments (regional scale), were sampled for aquatic macro-invertebrates. Eleven environmental variables (i.e. pH, DO, velocity, temperature, width, depth, TSS, BOD, COD, ammonia and canopy cover) were measured to assess their importance for local species richness. The average species richness was 34.9 species per region and the average abundance was 1380 individual per region. The highest number of species was 41, while the lowest species richness was 31. We applied local-regional richness regression models to explore the nature of the RSR–LSR relationship and then used variation partitioning to determine the relative importance of RSR and environmental conditions on LSR. We found a linear RSR–LSR relationship, which indicates unsaturated communities for macro-invertebrates in Malaysian streams and absence of local control with strong effects of regional processes. Variation in LSR explained by RSR was 43%, while the variation fraction in LSR explained by environmental conditions was low (2%) and not significant. We conclude that the variation in LSR is mainly controlled by the regional diversity pool (i.e. RSR) for aquatic macro-invertebrates in Peninsular Malaysia. However, weak effects of environmental conditions may reflect relatively low variability in the habitat among investigated streams. Further studies at larger scales, and involving different regions in this area, will be useful to draw comprehensive conclusions about determinants of local species diversity for stream invertebrates.